Comparison of five advanced oxidation processes for degradation of pesticide in aqueous solution - Affam, A.C. (Diponegoro University, 2018)
The study compared the technical efficiency and economic cost of five advanced oxidation processes (Fenton, UV photo-Fenton, solar photo-Fenton, UV/TiO2/H2O2 and FeGAC/H2O2) for degradation of the pesticides chlorpyrifos, cypermethrin, and chlorothalonil in aqueous solution. The highest degradation in terms of COD and TOC removals and improvement of the biodegradability (BOD5/COD ratio) index (BI) were observed to be (i) Fenton-69.03 (COD), 55.61 (TOC), and 0.35 (BI); (ii) UV photo-Fenton-78.56 (COD), 63.76 (TOC) and 0.38 (BI); (iii) solar photo-Fenton-74.19 (COD), 58.32 (TOC) and 0.36 (BI); (iv) UV/TiO2/H2O2-53.62 (COD), 21.54 (TOC), and 0.26 (BI); and (v) the most tech-nical efficient and cost effective process was FeGAC/H2O2. At an optimum condition (FeGAC 5 g/L, H2O2 100 mg/L, and reaction time of 60 min at pH 3), the COD and TOC removal efficiency were 96.19 and 85.60, respectively, and the biodegradation index was 0.40. The degradation rate constant and cost were 0.0246 min-1 and 0.74/kg TOC, respectively. The FeGAC/H2O2 process is the most techni-cally efficient and cost effective for pretreatment of the pesticide wastewater before biological treat-ment. Copyright Â© 2018 BCREC Group. All rights reserved.